CLINICAL CHARACTERISTICS OF COVID-19 IN CHILDREN OF DIFFERENT AGE GROUPS - Kramarov, S.O.; Seriakova, I.Yu.; Yevtushenko, V.V.; Shpak, I.V.; Shadrin, V.O.; Doroshenko, V.O.; Kyrytsia, N.S. (World of Medicine and Biology, 2022)
The study is devoted to accessing the clinical and epidemiological features of the coronavirus infection in children of different ages who were hospitalized during the 2020–2021 outbreaks of the epidemic. A retrospective analysis of 530 case histories of children under the age of 18 with coronavirus infection was conducted. The study revealed the predominance of general infectious symptoms and manifestations of upper respiratory tract lesions in children of all ages. A more severe course of the disease was registered in older children and was associated with the lower respiratory tract involvement. Children aged 1 month had relatively lower risks of lower respiratory tract injury compared to other age groups. We also found relatively higher levels of leukocytes, platelets and procalcitonin in children of this age.